Architecture of Belonging: The "Resilience Table" Model for Community Connection and Innovation - Irina Busurina (TGO Journal of Community Development, 2025)
This article introduces the “Resilience Table” model, an innovative urban planning framework aimed at strengthening community connection and collective resilience through intentional hospitality and creative approaches to designing urban spaces that foster belonging. Combining urban design principles, technological tools, participatory art installations, and analog reciprocity mechanisms, the model cultivates social bonds, civic engagement, and innovation. Drawing from recent urban belonging theories, it situates the Resilience Table within inclusive urban citizenship frameworks, social infrastructure theory, and participatory engagement practices. Employing a mixed-methods design—qualitative case studies, participatory observation, and literature review—the study evaluates the model's efficacy in nurturing inclusive, adaptive, and sustainable communities. Findings reveal that integrating digital networking, physical offer–exchange boards, and leadership opportunities enhances belonging and mutual support. The paper argues for embedding multi-modal hospitality as a strategic tool in urban planning to counter social fragmentation and build resilient, participatory cities.